HAK NAFKAH ANAK AKIBAT PERCERAIAN - Bambang Ali Kusumo, Nur Cholifah & (Wacana Hukum, 2011)
AbstractProvision of living child after the divorce is the duty of parents, especially fathers, In prctice the father of the obligations does not conform to the religious court’s decition. Given this, the parties raising and educating children should be proactively reminded to fulfill its obligations and the religious must be proactive to oversee the execution of its decition. Key words: a living child,  religious court decition.